Manajemen Strategi Dalam Menghadapi Persaingan Bisnis Pada Maskapai Garuda Indonesia di Bandara Internasional I Gusti Ngurah Rai Denpasar - Ida Ayu Trisna Wijayanthi; Ni Putu Ani Suanendri (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract. The tourism industry is very important in the country's economy, especially the island of Bali. This is dominated by air routes or airports, namely I Gusti Ngurah Rai International Airport. The existence of an airline or flight plays an important role in visiting trips. One of the biggest airlines